Trend of antibiotics usage in acute biliary pancreatitis, single centre experience - Alshaikh, Abdulrahman F.; Akbar, Layla H.; Abdulhadi, Layan H.; Tooq, Abrar A.; Aldawood, Fatimah F. (International Surgery Journal, 2022)
Background: Acute pancreatitis (AP) is associated with multiple morbidities and mortalities. The most common cause of AP cases in Bahrain are of biliary cause. At our institution, there is no clear data on the usage of antibiotics in AP. The clinical and financial impact of our practice is not fully understood. This research project aims at providing clear data to answer pivotal questions, such as; how often do we use antibiotics for ABP patients, what are the indications and what are the outcomes of such practice? It will also shed some light on the level of physicians’ adherence to the recent guidelines. Methods: This is a cross-sectional study. All cases admitted with ABP to the Salamaniya Medical Complex (SMC) during the years 2019 and 2020 were evaluated for relevant variables, data was then evaluated. Results: The percentage of patients who received antibiotics during their admission for ABP was 60.8% (38 patients out of 64 received antibiotics). Conclusions: The practice of using antibiotics in ABP is common at our institution. It is our observation that this practice is due to the over-diagnosis of acute cholecystitis during the same setting of ABP. Other explanations are the tendency of our surgeons to put patient who have significant co-morbidities on antibiotic therapy in anticipation of a severe disease. Further research is needed to explore this trend.